A simplified method for the analysis of urinary cotinine by GC-MS - Luiz Carlos Cunha; Fernando Gomes Ferreira Oliveira; Luciano Ressurreição dos Santos; Liuba Laxor Pucci; Jerônimo Raimundo Oliveira Neto; Rosemar Macedo Sousa Rahal; Ruffo Freitas Júnior (São Paulo State University (UNESP), 2013)
Cotinine is the major metabolite of nicotine and, being very stable and having a long biological half-life, it can be used as a biomarker for tobacco exposure. The aim of this study was to develop an analytical GC-MS technique to measure levels of cotinine in the urine of active and passive smokers and to compare the results with reference values. The extraction of cotinine to generate the calibration curve was performed by mixing urine (250 µL) with 50 µL of a cotinine standard, 50 µL of an internal standard of deuterated cotinine (15 µg∙mL-1) and 50 µL of 10% NH4OH solution. Next, 2 mL of a mixture of MTBE:dichloromethane:ethyl acetate (30:30:40 by volume) was added and the whole was vortexed, then centrifuged at 3000 rpm. Finally, 1.6 mL of the organic layer was evaporated under a stream of dry air at 50 °C. The resulting extract was dissolved in methanol and injected into the GC-MS system. The LOQ and LOD for cotinine were 100 and 20 ng∙mL-1, respectively. The curve was linear over the whole tested range of 100 - 5000 ng∙mL-1 and the method achieved 50% recovery. The intra and inter-day precisions were 1.62 - 7.28% and 0.86 - 2.68%, respectively. Accuracy was determined at three concentrations (low, medium and high), with six replicates (95.24 - 97.67%). The validation of this cotinine assay by GC-MS showed that it exhibited satisfactory limits and the assay could be performed with a one-step liquid-liquid extraction. The technique presented here can thus be used for the quantitation of cotinine levels in the urine of passive and active smokers.